Eruptive Seborrheic Keratoses Are Associated With a Co-Occurring Malignancy in the Majority of Reported Cases: A Systematic Review. Issue 1 (January 2022) - Mirali, Sara; Mufti, Asfandyar; Lansang, Rafael Paolo; Sachdeva, Muskaan; Yeung, Jensen
Background: Eruptive seborrheic keratoses (ESK) is a benign skin condition that has been associated with malignant and nonmalignant diseases. We conducted a systematic review of reported cases of ESK to identify and summarize associated comorbidities. Methods: MEDLINE and Embase were searched from database inception (1946) to July 31, 2020 for original articles describing ESK with or without a co-occurring condition. Subject demographics, as well as details of ESK and associated diagnoses were extracted from 76 articles (70 case reports, 3 case series, 3 case control studies) representing 92 patients. Results: In total, 76.1% ( n = 70/92) of patients with ESK had a co-occurring malignancy, 4.3% ( n = 4/92) presented with a nonmalignant condition, 9.8% ( n = 9/92) experienced ESK as an adverse drug reaction, and 9.8% ( n = 9/92) did not report any underlying medical condition. ESK preceded a cancer diagnosis in 76.1% ( n = 70/92) of patients with a mean latency period of 4.0 months (range: 0.25-9 months). The most common malignancies associated with ESK were cutaneous T-cell lymphoma ( n = 10/70, 14.3%) and gastrointestinal adenocarcinoma ( n = 9/70, 12.9%). ESK preceded nonmalignant conditions or no disease in 14.1% ( n = 13/92) of patients with a mean latency period of 3.1 months (range: 0.75-6 months). Drug-induced ESK occurred in 9.8% ( n = 9/92) of patients with a mean latency period of 7.1 weeks after changing medication. Conclusion: Although the role of ESK as a paraneoplastic cutaneous marker is debated, healthcare providers should consider screening for underlying malignancy in patients presenting with ESK. Larger studies are needed to confirm its role as a marker for disease.